2006
DOI: 10.1016/s0140-6736(06)68812-0
|View full text |Cite
|
Sign up to set email alerts
|

Specialist outreach to isolated and disadvantaged communities: a population-based study

Abstract: BackgroundVisiting-specialist clinics (specialist outreach) have the potential to overcome some of the substantial access barriers faced by disadvantaged rural, remote, and Indigenous communities, but the effectiveness of outreach clinics has not been assessed outside urban and non-disadvantaged settings. We aimed to assess the effects of outreach clinics on access, referral patterns, and care outcomes in remote communities in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(115 citation statements)
references
References 14 publications
2
111
0
2
Order By: Relevance
“…In the fi rst 3 years, substantial improvement in indicators of access was shown, the need for remote people to travel was reduced, and specialists, health workers, and patients expressed positive attitudes towards the service. 69 In the early years of the service, especially at the time it was launched, national and territory goverments, health-service managers, professional medical societies, Indigenous organisations, and specialists themselves were powerful positive drivers because they celebrated a seemingly worthwhile initiative and enjoyed good publicity. Indigenous communities and remote clinical staff were supportive but less infl uential.…”
Section: Specialist Outreach To Remote Indigenous Communities In Austmentioning
confidence: 99%
“…In the fi rst 3 years, substantial improvement in indicators of access was shown, the need for remote people to travel was reduced, and specialists, health workers, and patients expressed positive attitudes towards the service. 69 In the early years of the service, especially at the time it was launched, national and territory goverments, health-service managers, professional medical societies, Indigenous organisations, and specialists themselves were powerful positive drivers because they celebrated a seemingly worthwhile initiative and enjoyed good publicity. Indigenous communities and remote clinical staff were supportive but less infl uential.…”
Section: Specialist Outreach To Remote Indigenous Communities In Austmentioning
confidence: 99%
“…Surgical camps and these outreach programs from the national hospital are dependent on funding from the Ministry of Health, which limits their frequency. Studies have shown that outreach can be an effective policy to improve access to specialist care in rural areas, where referral is practically a ''myth'' [27].…”
Section: Policies To Overcome Maldistribution Of Surgical Workforcementioning
confidence: 99%
“…5 Inequalities in the social determinants of health between metropolitan and rural populations influence the need for health care. 4,6 Although it is a developed country, Australia continues to have problems addressing the high rate of preventable disease, particularly in remote communities where the proportion of indigenous people is high and where geographical distances are extremely large. 4 For example, the rates of trachoma, 7 otitis media 8 and rheumatic heart disease 9 in these communities remain high relative to global expectations.…”
Section: Introductionmentioning
confidence: 99%
“…12 However, only 15% of Australian specialists have their main practice outside metropolitan areas, whereas 30% of Australians reside in nonmetropolitan areas. 13 Rural specialist outreach services could help overcome complex barriers to service access, 4,6 which are mainly due to language and cultural differences, 5,14 and help avoid the cost and effort of seeking care away from home. 15 Visiting specialists can meet many of the health service needs of rural areas 16 and, since they are less exposed to some of the negative effects of full-time rural specialist practice, it may be easier to recruit them.…”
Section: Introductionmentioning
confidence: 99%